Produccion de hojarasca de los manglares de la Isla de San Andres, Caribe colombiano - Garcia Hansen, I.=700 1 Gaviria Chiquazuque, J.F.; Prada Triana, M.C.
(Es, En)
ilus., 26 ref.
Keywords: HOJARASCA; ECOSISTEMA; MANGLES; MATERIA ORGANICA DEL SUELO; RHIZOPHORA MANGLE; AVICENNIA; CARIBE; COLOMBIA